Pengaruh Dual-Task Training (Motor-Cognitive) terhadap Keseimbangan Dinamis pada Anak Usia Sekolah - Yulinar Anwar (Universitas Widya Husada Semarang, 2019)
Background : School-age Children are characterized by agile movements and motor activity coupled with the need to begin exploring the environment so that motor skills are needed. One aspect of motor skills is dynamic balance. Dual-task training (motor-cognitive) is a method of training that combines motor and cognitive tasks. The purpose of this exercise is to activation pattern of circuits in brain to achieve an adaptive system so that automation can be generated which can affect dynamic balance. Methods : this research is experimental quasi with time series design. The sampling technique used purposive sampling with a sample size of 30 students in 10- and 11- years-old who were not flat foot, not obese, and did not experience balance disorders. Primary data collection is obtained through dynamic balance instruments with balance beam walking test. The collected data used Shapiro Wilk for the normality test and obtained a value of p <0.05, which means that the distribution of data is abnormally distributed then a difference test of the of the pre-test and post-test using Friedman post hoc Wilcoxon Test. Results : the study was conducted for four weeks with 12 training sessions. The result of the analysis were started from pre-test, post-test 1, post-test 2, post-test 3, and post-test 4. The results overall showed a changed in dynamic balance between before and after 12 times of exercise with a significant value p=0,0001 (p <0,05). Conclusion : Therefore, it can be conclused that there is an effect of dual-task training (motor-cognitive) to dynamic balance of school-age children. Keywords : Dual-Task Training (Motor Cognitive), Dynamic Balance, School-age Children